2017
DOI: 10.1080/07315724.2017.1357509
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cranberry Juice Enriched with Omega-3 Fatty Acids Adjunct with Nonsurgical Periodontal Treatment on Metabolic Control and Periodontal Status in Type 2 Patients with Diabetes with Periodontal Disease

Abstract: Consumption of cranberry juice enriched with omega-3 can be beneficial as adjuvant therapy with nonsurgical periodontal therapy in decreasing glycated hemoglobin, increasing HDL-C, and improving periodontal status in patients with diabetes with periodontal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 46 publications
1
48
0
Order By: Relevance
“…CrB extracts (CrBEs) also halted visceral adiposity and weight gain in HFD-fed C57BL/6J mice, and improved HFD-induced hypercholesterolemia, hypertriglyceridemia, antioxidant defense mechanisms, and hepatic oxidative stress and normalized the NF-κB/IκB ratio [ 54 ]. Long-term CrBE consumption effects were also investigated [ 55 , 63 ], and the addition of CrBE to normal chow delayed age-related basal plasma insulin concentration declines [ 63 ]. CrBE supplementation also improved glucose responsiveness and increased insulin concentrations (7.6%) in rats, without significant HOMA-IR changes.…”
Section: Cranberriesmentioning
confidence: 99%
See 1 more Smart Citation
“…CrB extracts (CrBEs) also halted visceral adiposity and weight gain in HFD-fed C57BL/6J mice, and improved HFD-induced hypercholesterolemia, hypertriglyceridemia, antioxidant defense mechanisms, and hepatic oxidative stress and normalized the NF-κB/IκB ratio [ 54 ]. Long-term CrBE consumption effects were also investigated [ 55 , 63 ], and the addition of CrBE to normal chow delayed age-related basal plasma insulin concentration declines [ 63 ]. CrBE supplementation also improved glucose responsiveness and increased insulin concentrations (7.6%) in rats, without significant HOMA-IR changes.…”
Section: Cranberriesmentioning
confidence: 99%
“…Serum HbA1c levels were reduced by 11.4% and 6.02% following RCCJ and RCCJ enriched with omega-3 fatty acid consumption. Omega-3 fatty acid-enriched RCCJ also increased HDL-C levels by 21.1% compared with the baseline [ 63 ]. Additionally, folic acid consumption combined with LCCJ decreased plasma homocysteine levels and increased adiponectin and folic acid levels without any change in inflammatory biomarker levels (IL-6, IL-10, IL-18, and TNF-α) [ 66 ].…”
Section: Cranberriesmentioning
confidence: 99%
“…Second, after screening the full texts of the remaining 13 articles, four reports were excluded for irrelevant outcome measurement [ 50 ], insufficient inclusion criteria [ 40 , 51 ], and inappropriate study design [ 52 ] ( Table S1 ). Finally, nine eligible reports from eight studies [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ] were included in this systematic review (inter-reviewer agreement, kappa statistic = 0.81). Among the nine reports included, two reports [ 57 , 60 ] had data generated from a single study conducted by Javid et al [ 57 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…The beneficial influence of diets enriched in proanthocyanidins from cranberry juice and fish oil on both insulin and lipoprotein metabolisms were also found in patients with diabetes and periodontal disease since this mixture of nutrients decreased glycated hemoglobin and increased HDL-C, while improving periodontal status in those patients [ 59 ]. It was also reported that the postprandial chylomicron response to acute or chronic fish oils plus polyphenols intake is different and even opposite [ 60 ], adding an extra layer in the complex effects of the nutritional intervention with these food compounds.…”
Section: Combined Polyphenols and Fish Oils Intake For Improving Metabolic Healthmentioning
confidence: 99%